Lateral Habenula Inactivation Alters Willingness to Exert Physical Effort Using a Maze Task in Rats - Sevigny, Joshua P.; Bryant, Emily N.; Encarnacion, Érica; Smith, Dylan F.; Acosta, Rudith; Baker, Phillip M. (Frontiers in Behavioral Neuroscience, 2021)
An impairment in willingness to exert physical effort in daily activities is a noted aspect of several psychiatric conditions. Previous studies have supported an important role for the lateral habenula (LHb) in dynamic decision-making, including decisions associated with discounting costly high rewards. It is unknown whether a willingness to exert physical effort to obtain higher rewards is also mediated by the LHb. It also remains unclear whether the LHb is critical to monitoring the task contingencies generally as they change, or whether it also mediates choices in otherwise static reward environments. The present study indicates that the LHb might have an integrative role in effort-based decision-making even when no alterations in choice contingencies occur. Specifically, pharmacological inactivation of the LHb showed differences in motivational behavior by reducing choices for the high effort (30cm barrier) high reward (2 pellets) choice versus the low effort (0 cm) low reward (1 pellet) choice. In sessions where the barrier was removed, rats demonstrated a similar preference for the high reward arm under both control and LHb inactivation. Further, no differences were observed when accounting for sex as a biological variable. These results support that effort to receive a high value reward is considered on a trial by trial basis and the LHb is part of the circuit responsible for integrating this information during decision-making. Therefore, it is likely that previously observed changes in the LHb may be a key contributor to changes in a willingness to exert effort in psychiatric conditions.